The safety of fishery products - Adrian Zugravu Gheorghe; Maria Magdalena Turek Rahoveanu; Adrian Turek Rahoveanu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
The paper follows two main objectives: to understand consumers' perception and image of fishery products and to identify communication levers in order to improve the perceived image of fishery products. Orientations in terms of communication are product-focused and aim at enhancing the reputation of products, consequently with impact on product consumption. The present research is focused on the fishery products, regardless of their presentation - fresh, frozen or processed. This paper conducted a questionnaire survey of Romanian consumers' perception toward fishery products. The empirical study with brands indicated that consumers are different awareness to domestic and foreign safety fish products. National fishery products got more attention from the consumers. Foreign fishery products had higher perceptive price, but Romanian fishery products acquired higher safety perceptive value, and got a better rank in the preference list and in the purchase intention of the consumers.
Keywords: 330; fishery products perception; perceptive price; image of fish products